Uso de Saccharomyces cerevisiae en la producción de pollos - Chasoy Miranda., Cristian Rolando (2021)
The present study aims to analyze the results obtained within the feeding of broilers using Saccharomyces cerevisiae as a food supplement, throughout history humans have used it in the production of various products such as the preparation of bread, wine and beer, currently its use is very common for feeding various animals such as pig and chicken, within the present analysis chickens that have been fed in a traditional way and chicken that have been fed with Brewer's yeast, this is given to analyze what is the incidence or change that exists between the types of diet, resulting in weight gain with the use of Treatment 3 with Saccharomyces cerevisiae compared to normal feeding, so if a Broiler chicken is fed from day 1 with Saccharomyces cerevisiae at the end of 42 days its average weight can reach 3019.9 0 grams, this means that on day 42, chicken with greater weight will be obtained, since each chicken must have a food plan that involves balanced and Saccharomyces cerevisiae.